2012
DOI: 10.1007/s10880-012-9317-0
|View full text |Cite
|
Sign up to set email alerts
|

Recruiting Young Adult Cancer Survivors for Behavioral Research

Abstract: Young adults have been dramatically underrepresented in cancer survivorship research. One contributing factor is the difficulty recruiting this population. To identify effective recruitment strategies, the current study assessed the yield of strategies used to recruit young survivors for an exercise intervention including: clinic-based recruitment, recruitment at cancer-related events, mailings, telephone-based recruitment, advertising on the internet, radio, television and social networking media, distributin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

5
74
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 66 publications
(80 citation statements)
references
References 10 publications
5
74
0
Order By: Relevance
“…[5][6][7][8][9][10] Our limited understanding of how best to address these and other long-term survivorship care needs may be partly related to difficulties recruiting young survivors for research studies. [11][12][13][14] Several factors contribute to recruitment challenges in AYA-aged survivors. [11][12][13][14] Since they constitute only 5% of the cancer survivor population in the United States, 15 the number of AYA-aged survivors seen at individual medical facilities is limited.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…[5][6][7][8][9][10] Our limited understanding of how best to address these and other long-term survivorship care needs may be partly related to difficulties recruiting young survivors for research studies. [11][12][13][14] Several factors contribute to recruitment challenges in AYA-aged survivors. [11][12][13][14] Since they constitute only 5% of the cancer survivor population in the United States, 15 the number of AYA-aged survivors seen at individual medical facilities is limited.…”
mentioning
confidence: 99%
“…[11][12][13][14] Several factors contribute to recruitment challenges in AYA-aged survivors. [11][12][13][14] Since they constitute only 5% of the cancer survivor population in the United States, 15 the number of AYA-aged survivors seen at individual medical facilities is limited. While cancer cooperative groups provide infrastructure for studies with multi-site recruitment, most of these studies focus on treatment 16 and these groups are less focused on studying survivorship issues.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Rabin et al (2013) extended the work of Zebrack's study to conduct an in-depth qualitative study with 20 YACS and found that programs involving PA, relaxation, emotional support, information, nutrition/weight management, and similarity with other participants were the common program categories that might promote physical and emotional health for YACS. Taken together, there appears to be a strong need for interventions tailored to the needs of this demographic.…”
Section: Correlates Of Successmentioning
confidence: 88%
“…Rabin et al (2013) conducted semi-structured interviews in an exploratory qualitative study with 20 YACS about intervention preferences and the emerging themes were that interventions should work with competing obligations (such as work and family) and that interventions should also provide social support. Zebrack, Bleyer, Albritton, Medearis and Tang (2006) studied 37 YACS to assess health and supportive care needs and found that 96% ranked meeting other survivors as a top five need.…”
Section: Correlates Of Successmentioning
confidence: 99%